Isolation and characterization of SSR and EST‐SSR loci in Chamaecyparis formosensis (Cupressaceae) - Huang, Chiun‐Jr; Chu, Fang‐Hua; Liu, Shau‐Chian; Tseng, Yu‐Hsin; Huang, Yi‐Shiang; Ma, Li‐Ting; Wang, Chieh‐Ting; You, Ya Ting; Hsu, Shuo‐Yu; Hsieh, Hsiang‐Chih; Chen, Chi‐Tsong; Chao, Chi‐Hsiang (Applications in plant sciences, 2018)
Premise of the Study Simple sequence repeat (SSR) and expressed sequence tag (EST)–SSR markers were developed as tools for marker‐assisted selection of Chamaecyparis formosensis and for the molecular differentiation of cypress species. Methods and Results Based on the SSR‐enriched genomic libraries and transcriptome data of C. formosensis, 300 primer pairs were selected for initial confirmation, of which 19 polymorphic SSR and eight polymorphic EST‐SSR loci were chosen after testing in 92 individuals. The number of alleles observed for these 27 loci ranged from one to 17. The levels of observed and expected heterozygosity ranged from 0.000 to 1.000 and from 0.000 to 0.903, respectively. Most markers also amplified in C. obtusa var. formosana. Conclusions The developed SSR and EST‐SSR sequences are the first reported markers specific to C. formosensis. These markers will be useful for individual identification of C. formosensis and to distinguish cypress species such as C. obtusa var. formosana.